Diversity and interdisciplinarity in nanoscience and nanotechnology: a time-related analysis of the subject category - Finardi, Ugo; Lamberti, Carlo (Journal of nanoparticle research : an interdisciplinary forum for nanoscale science and technology, 2021)
Nanosciences and nanotechnologies (NST) are known for their potentialities, as well as for their interdisciplinarity, due to their exploitation of their specific approach in different scientific fields. The aim of the present paper is to study the evolution of interdisciplinarity in NST. Its experimental activity is based on the data of the “NANOSCIENCE & NANOTECHNOLOGY” (N&N) “Web of Science™” subject category. This subject category, launched in 2005, collects the relevant NST scientific literature and is thus an instrument apt to its analysis. The article uses data of the accessory subject categories of the journals belonging to N&N to calculate several diversity indicators, able to disentangle its interdisciplinary features. Results show that the main evolution in such terms is in the first years since its inception, while the situation in the 2010s is more stable. Nevertheless, analysis of data shows also a lack of balance between the accessory subject categories.